Utilizing Bulu Clam Shell and Sikacim Concrete as Partial Cement Replacement in Porous Concrete Production - Z, Fynnisa; Muhammad Irwansyah; Moraida Hasanah; Nur Haliza; Sophia Az-Zahra P (Faculty of Science and Technology Universitas Islam Negeri Ar-Raniry, 2025)
Abstract: The novelty of this research lies in the utilization of waste from bulu clam shells, which are abundantly found in Batu Bara Regency, North Sumatra, Indonesia, combined with Sikacim as a partial substitute for cement in the production of pervious concrete. Bulu clam shells are waste materials with a high calcium carbonate (CaO) content. The development of compressive strength and porosity characteristics of pervious concrete is the main objective of this study. Therefore, this research employs bulu clam shell waste and Sikacim as partial replacements for cement in the production of pervious concrete to minimize the environmental impact of waste. The methodology refers to ACI 522R-10 with a curing age of 28 days. The test specimens were cylindrical with a diameter of 15 cm and a height of 30 cm. The mix variations of pervious concrete in comparison to cement:shell:Sikacim were (100:0:0; 95:5:0; 95:0:5; 90:10:0; 90:0:10; 90:5:5)%. SEM analysis indicates that bulu clam shell waste exhibits a characteristic aragonite morphology, marked by needle-like and rough surface textures. XRF analysis shows that bulu clam shell waste has significant potential for various industrial applications due to its high CaO content and the presence of other supporting elements such as Al₂O₃ and SiO₂. The porosity test results of pervious concrete show that the addition of Sikacim tends to increase porosity, particularly at a dosage of 5%, reaching 27.3%. In contrast, the addition of bulu clam shell waste reduces porosity due to its ability to fill micro-pores. The compressive strength test results demonstrate that bulu clam shell waste is highly effective in increasing the compressive strength of pervious concrete, especially at a 10% composition, achieving 8.86 MPa, which represents a 1.7% increase compared to normal concrete. It can be concluded that bulu clam shell waste has strong potential for the development of the construction industry, as it can partially replace cement while also serving as a more environmentally friendly concrete material. Abstrak: Penelitian Kebaruan penelitian adalah memanfaatkan limbah dari cangkang kerang bulu, yang banyak ditemukan di Kabupaten Batu Bara, Sumatera Utara, Indonesia, ditambah dengan sikacim sebagai pengganti sebagian penggunaan semen pada pembuatan beton berpori. Pengembangan sifat kuat tekan dan porositas beton berpori merupakan tujuan penelitian, sehingga penelitian memanfaatkan limbah cangkang kerang bulu dan Sikacim sebagai pengganti sebagian semen dalam produksi beton berpori untuk meminimalkan dampak lingkungan dari limbah. Metode yang digunakan mengacu pada ACI 522R-10, dengan umur pengujian 28 hari. Sampel uji berbentuk silinder, dengan diameter 15 cm dan tinggi 30 cm. Hasil pengujian SEM menunjukkan cangkang kerang bulu memiliki morfologi aragonit yang khas, ditandai dengan tekstur seperti jarum dan kasar. Analisis XRF menunjukkan cangkang kerang memiliki potensi signifikan untuk berbagai aplikasi industri karena kandungan CaO yang tinggi dan adanya unsur pendukung lainnya seperti Al₂O₃ dan SiO₂. Uji porositas beton berpori menunjukkan penambahan Sikacim cenderung meningkatkan porositas, terutama pada dosis 5% sebesar 27,3%. Penambahan cangkang kerang bulu mengurangi porositas karena kemampuannya mengisi pori-pori mikro. Hasil uji kekuatan tekan menunjukkan cangkang kerang bulu sangat efektif dalam meningkatkan kekuatan tekan beton berpori, khususnya pada komposisi 10%, sebesar 8,86 Mpa, meningkat sebesar 1,7% dari nilai beton normal. Hasil penelitian dapat disimpulkan bahwa limbah cangkang kerang bulu memiliki potensi dalam pengembangan industri konstruksi, karena dapat sebagian menggantikan semen sekaligus berfungsi sebagai material beton yang lebih ramah lingkungan.